Long-term efficacy, safety, and patient-reported outcomes of apitegromab in patients with spinal muscular atrophy: results from the 36-month TOPAZ study - Crawford, Thomas O.; Day, John W.; De Vivo, Darryl C.; Krueger, Jena M.; Mercuri, Eugenio; Nascimento, Andres; Pasternak, Amy; Mazzone, Elena Stacy; Duong, Tina; Song, Guochen; Marantz, Jing L.; Baver, Scott; et al. (Frontiers in Neurology, 2024)
Background and purpose: At 12 months in the phase 2 TOPAZ study, treatment with apitegromab was associated with both an improved motor function in patients with Type 2 or 3 spinal muscular atrophy (SMA) and with a favorable safety profile. This manuscript reports the extended efficacy and safety in the nonambulatory group of the TOPAZ study at 36 months.: Patients who completed the primary study (NCT03921528) could enroll in an open-label extension, during which patients received apitegromab 20 mg/kg by intravenous infusion every 4 weeks. Patients were assessed periodically via the Hammersmith Functional Motor Scale-Expanded (HFMSE), Revised Upper Limb Module (RULM), World Health Organization (WHO) motor development milestones, Pediatric Evaluation of Disability Inventory Computer Adaptive Test (PEDI-CAT) Daily Activities and Mobility domains, and Patient-Reported Outcomes Measurement Information System (PROMIS) Fatigue questionnaire. Results: Of the 58 patients enrolled in TOPAZ, 35 were nonambulatory (mean age 7.3 years). The mean change at 36 months in HFMSE score from baseline was +4.0 (standard deviation [SD]: 7.54), and +2.4 (3.24) for RULM score (excluding n = 7 after scoliosis surgery). Caregiver-reported outcomes (PEDI-CAT and PROMIS Fatigue) showed improvements from baseline over 36 months.In addition, most patients (28/32) improved or maintained WHO motor milestones achieved at baseline. The most frequently reported treatment-emergent adverse events were pyrexia (48.6%), nasopharyngitis (45.7%), COVID-19 infection (40.0%), vomiting (40.0%), and upper respiratory tract infection (31.4%).The benefit of apitegromab treatment observed at 12 months was sustained at 36 months with no new safety findings.